DESIGN AND FABRICATION OF PLATFORM FLUIDS FOR DROPLET GENERATOR APPLICATIONS - Azhar Fa'iq, Muhammad
Microfluidics is a field of science and technology that focuses on the processing and manipulation of liquids or fluids with a scale of 10-9 to 10-18 liters. Microfluidic systems can be divided into several types based on the flow of the fluid such as droplet-based microfluids. Droplet-based microfluids utilize two types of immiscible fluids to form a discrete flow that resembles a droplet. This kind of flow is achieved using droplet generator. Droplet-based microfluidic systems are widely used in research and industry due to the various fluid flow properties that aid in analysis and manufacturing. Despite having various advantages, microfluidic